2017
DOI: 10.3389/fpls.2016.02068
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacterium Pseudomonas fluorescens RG11 May Transform Tryptophan to Melatonin and Promote Endogenous Melatonin Levels in the Roots of Four Grape Cultivars

Abstract: Endophytes have been verified to synthesize melatonin in vitro and promote abiotic stress-induced production of endogenous melatonin in grape (Vitis vinifera L.) roots. This study aimed to further characterize the biotransformation of tryptophan to melatonin in the endophytic bacterium Pseudomonas fluorescens RG11 and to investigate its capacity for enhancing endogenous melatonin levels in the roots of different grape cultivars. Using ultra performance liquid chromatography-tandem mass spectrometry combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 76 publications
3
56
1
Order By: Relevance
“…Therefore, it becomes clear that endophytic bacteria have the potential for MEL synthesis via host‐plant interactions. The enhanced in vitro MEL biosynthesis in the roots of different grape cultivars by endophytic bacterium Pseudomonas fluorescens (RG11) under salt stress conditions has been observed . This study further adds to the existing knowledge on endogenous phytomelatonin biosynthesis by rhizobacteria in plants when exposed to abiotic stress.…”
Section: Mel Regulates Plant‐rhizomicrobial Interactionsmentioning
confidence: 57%
See 2 more Smart Citations
“…Therefore, it becomes clear that endophytic bacteria have the potential for MEL synthesis via host‐plant interactions. The enhanced in vitro MEL biosynthesis in the roots of different grape cultivars by endophytic bacterium Pseudomonas fluorescens (RG11) under salt stress conditions has been observed . This study further adds to the existing knowledge on endogenous phytomelatonin biosynthesis by rhizobacteria in plants when exposed to abiotic stress.…”
Section: Mel Regulates Plant‐rhizomicrobial Interactionsmentioning
confidence: 57%
“…Evolutionary evidence has suggested that many land plants establish symbiotic relations with diverse microbes, such as bacteria, fungi, and actinomycetes, all of which can dwell in their roots and other organs . Studies have established the beneficial aspects of plant‐microbes in terms of providing a shield against phyto‐pathogens while negating the ill effects of stresses .…”
Section: Mel Regulates Plant‐rhizomicrobial Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[67][68][69]. Furthermore, several investigations have studied the role of endophytic rhizobacteria in the reinforcement ability of plants to produce melatonin [70,71]. In addition, melatonin inhibited the total microorganisms, including mold, yeast, and bacteria, in stored apple juice during the storage time (4-12 h) [72].…”
Section: Antifungal Effect Of Melatoninmentioning
confidence: 99%
“…When grapewine roots are exposed to salinity or drought stress colonized by B. amyloliquefaciens SB‐9, it increases the production of melatonin and also its intermediates. It was found that endophytic bacteria Pseudomonas fluorescens RG11 is able to produce melatonin and enhance endogenous melatonin in Vitis vinifera L. roots under abiotic stress …”
Section: Introductionmentioning
confidence: 99%